2008
DOI: 10.1111/j.1365-2664.2008.01486.x
|View full text |Cite
|
Sign up to set email alerts
|

Spider responses to alien plant invasion: the effect of short‐ and long‐term Chromolaena odorata invasion and management

Abstract: 1.Invasions by alien plants into unspoiled ecosystems are a cause for concern because the pristine systems are important stores of biodiversity. Indeed, the introduction of non-indigenous species into protected areas is a direct threat to conservation. Consequently, it is fundamental to document the impact that alien invasive plants have on native communities and to determine if, and at what rate, native communities re-establish following the removal of invasives. Chromolaena odorata is one of the most importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 23 publications
3
63
0
Order By: Relevance
“…A total of 38 PAs have been sampled, with 24 represented by >50 samples (Table 2). Species lists and diversity data of several reserves have been published: Ndumo Game Reserve Wesołowska & Haddad, 2009), Tembe Elephant Park , the Mkhuze Game Reserve and Phinda Private Game Reserve (Lovell et al, 2007), Hluhluwe/iMfolozi Park (Mgobozi et al, 2008;Ngome State Forest (Van der Merwe, 1994;Van der Merwe et al, 1996;Dippenaar-Schoeman et al, 2006b), and the iSimangaliso Wetland Park (Combrink, 2007;Combrink & Kyle, 2006).…”
Section: Kwazulu-natal Provincementioning
confidence: 99%
See 2 more Smart Citations
“…A total of 38 PAs have been sampled, with 24 represented by >50 samples (Table 2). Species lists and diversity data of several reserves have been published: Ndumo Game Reserve Wesołowska & Haddad, 2009), Tembe Elephant Park , the Mkhuze Game Reserve and Phinda Private Game Reserve (Lovell et al, 2007), Hluhluwe/iMfolozi Park (Mgobozi et al, 2008;Ngome State Forest (Van der Merwe, 1994;Van der Merwe et al, 1996;Dippenaar-Schoeman et al, 2006b), and the iSimangaliso Wetland Park (Combrink, 2007;Combrink & Kyle, 2006).…”
Section: Kwazulu-natal Provincementioning
confidence: 99%
“…are near endemic (Foord et al, 2011b). The Savanna Biome has been the most intensively studied in the Limpopo Province (Whitmore et al, 2001(Whitmore et al, , 2002aFoord et al, 2002Foord et al, , 2008Foord et al, , 2013Foord & Dippenaar-Schoeman, 2003;Dippenaar-Schoeman & Leroy, 2003;Modiba et al, 2005;Dippenaar et al, 2008;Muelelwa et al, 2010), but several studies have been published from KwaZulu-Natal (Lawrence et al, 1980;Haddad et al, , 2010Mgobozi et al, 2008), Mpumalanga (DippenaarSchoeman & Leroy, 2003;Robertson et al, 2011) and parts of Gauteng (Dippenaar-Schoeman et al, 1989). The potential of spiders to serve as diversity surrogates was investigated by Foord et al (2013), and spiders have also been included in several ecological studies on arthropods in the biome (Nicolai, 1989;Rivers-Moore & Samways, 1996;Blaum et al, 2009;Lovell et al, 2009Lovell et al, , 2010Jonnson et al, 2010).…”
Section: Savanna Biomementioning
confidence: 99%
See 1 more Smart Citation
“…For example, Heleno et al (2008) found a negative relationship between percent invasive plants and total species richness of both plants and insects on Sao Miguel island, part of the Azores archipelago. A number of other studies have also demonstrated a decrease in insect total abundance, species richness and diversity, and trophic and guild structure, particularly for herbivorous insects, in relationship to invasion by non-native plants (Mgobozi et al, 2008;Wu et al, 2009;Yoshioka et al, 2010;Simao et al, 2010).…”
Section: Introductionmentioning
confidence: 93%
“…The integration of both abiotic and biotic changes in the system via behavioral adaptations to vegetative structure and predation on lower trophic levels makes spiders useful as ecological indicators , DeVore 2011, Foelix 2011. Indeed, changes in spider communities often indicate greater changes in the ecosystem that supports these predators (Mgobozi et al 2008), so understanding the cascading effects of invasive plants on this trophic group becomes very important for ecologists and conservation biologists.…”
Section: Introductionmentioning
confidence: 99%